Stability of ex situ biological methanation of H2/CO2 with a mixed microbial culture in a pilot scale bubble column reactor. (June 2022) - Laguillaumie, Léa; Rafrafi, Yan; Moya-Leclair, Elisabeth; Delagnes, Delphine; Dubos, Simon; Spérandio, Mathieu; Paul, Etienne; Dumas, Claire
Graphical abstract: Highlights: Mixed Microbial Culture converted up to 94% H2 /CO2 into CH4 at 4NL.L −1 .d −1. Acetate and propionate accumulated when methanogens were grown nutrient-limited. Process was resilient to a 34d starvation period at 25 °C under N2 atmosphere. MBA03 association with Methanobacterium was an indicator of stable operation. Coprothermobacter was associated with Methanothermobacter when increasing gas load. Abstract: Biological methanation is a promising technology for gas and carbon valorisation. Therefore, process stability is required to allow its scale up and development. A pilot scale bubble column reactor was used for ex situ biological methanation with Mixed Microbial Culture (MMC). A 16S rRNA high throughput sequencing analysis revealed the MMC reached a stable composition with 50–60% Methanobacterium in closed liquid mode, a robust genus adapted to large scale constraints. Class MBA03 was identified as an indicator of process stability. Methanogenic genera moved toward 50% of Methanothermobacter when intensifying the process, and proteolytic activity was identified while 94% of H2 /CO2 was converted into methane at 4NL.L −1 .d −1 . This study gives clarifications on the origin of volatile fatty acids (VFA) apparitions. Acetate and propionate accumulated when methanogenic activity weakened due to nutritive deficiency, and when PH2 reached 0.7 bar. The MMC withstood a storage period of 34d at room temperature indicating its suitability for industrial constraints.